Executive Weapons to Combat Infection of the Art Market - Jennifer Anglim Kreder (Washington University Law Review, 2011)
Over the years, the executive branch has seized Nazi loot in various ways. The seizure that launched the modern Holocaust-era art movement was that accompanying the civil forfeiture proceeding filed in federal court in 1999 against Portrait of Wally, a painting by Egon Schiele. The seizure caused an uproar in the art world, which largely was concerned about future art loan prospects. At the time, there was a concern about the impact of the civil forfeiture seizure — despite the support for widespread restitution of Nazi-looted art —for fear of hindering State Department efforts to resolve remaining Holocaust-era issues globally and alienating museums and other possessors of tainted art, whose cooperation is essential for widespread restitution. Now that some prominent museums have demonstrated the lengths to which they will go to try to prevent objective resolution of claims, the issue has been cast in a whole new light: Should one feel sympathy about depriving obstinate possessors of Nazi-looted art of purported property rights pending resolution of colorable claims? The Portrait of Wally case recently settled for 19 million; without the seizure, we likely never would have seen the Washington Principles, the Vilnius Declaration, or the Terezín Declaration of 2009, all of which support undertaking and publicizing provenance research and restitution.
Keywords: Bennis v. Michigan 516 U.S. 442 (1996); Confiscations; Due process of law; Forfeiture; Looting; Restitution; Civil Asset Forfeiture Reform Act of 2000; United States